Specification for electromechanical components for electronic equipment: basic testing procedures and measuring methods. Impacttests (free components), static load tests (fixed components), endurance tests and overload tests. Test 10c Part 5 Supplement No. 2, (29th October 1982) - British Standards Institution,
No abstract available